Bank selection criteria of Nigerian residents in Ghana: a case study of traders and students in Kumasi - Jawol, King Wisdom (KNUST, 2024)
A thesis submitted to the Department Of Marketing And Corporate Strategy, School Of Business, KWAME NKRUMAH UNIVERSITY OF SCIENCE AND TECHNOLOGY, in partial fulfillment of the requirement for the award of masters degree of Masters of business administration